Optimizing the Role of LMKN in Managing Royalties for Songs and/or Music: A Comparative Study Between Indonesia and the United Kingdom - Setyo Nugraha; Ridha Wahyuni (Green Publisher Indonesia, 2026)
The centralization of one-stop royalty management through the Lembaga Manajemen Kolektif Nasional (LMKN) in Indonesia has triggered structural polemics, ranging from bureaucratic ineffectiveness to a crisis of trust among songwriters. Although the government has issued Regulation of the Minister of Law Number 27 of 2025 to strengthen supervision, the institutional framework that positions the state as an active operator still fails to address the root problems. This study analyzes the optimization of LMKN's role in the national music royalty ecosystem through a comparative examination of the institutional model in the United Kingdom. The research employs a normative-juridical method with statutory and comparative legal approaches, examining Law Number 28 of 2014 concerning Copyright and Government Regulation Number 56 of 2021, juxtaposed with the Copyright, Designs and Patents Act 1988 (CDPA 1988) of the United Kingdom. The results reveal that Indonesia's state-centered model imposes a dual burden on LMKN as both regulator and operator. In contrast, the United Kingdom's market-based model proves more effective by delegating operational functions to private institutions and adjudication to the Copyright Tribunal. This study recommends transforming LMKN into an independent, quasi-judicial supervisory body akin to the Copyright Tribunal, focusing on tariff dispute resolution and transparency audits, while returning royalty collection to a regulated market mechanism.​